2021
DOI: 10.1155/2021/5569872
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis Based on Intelligent Electronic Medical Arthroscopy for the Treatment of Varus Knee Osteoarthritis

Abstract: The incidence of inverted knee osteoarthritis is slowly increasing, there are technical limitations in the treatment, and the operation is difficult. In this article, we will study the benefits and costs of arthroscopic cleaning treatments based on intelligent electronic medicine. This article focuses on knee osteoarthritis patients in the EL database. There are 12 male patients, accounting for 66.67%, and 6 female patients, accounting for 33.33%. The average body mass index (BMI) of the patients was 28.08, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Considering that coronary sickness is very fragile to protect time, the time delay between information grouping, far-off transmission, and data accumulating ought to be seen as in the arrangement of information transmission and data storing limit modules. At the same time, to simplify it for the diagnosing expert to make heads or tails of the continuous situation of the patient more, the indispensably visual video transmission work is turned on when basic, and the truly visual video is shipped off the terminal of the astute clinical end system through the distant transmission module [ 15 ]. This module sends the data gathered by the versatile terminal to the data stockpiling and brilliant clinical handling terminal as quickly as time permits, which is more helpful for the acknowledgment of the well-being observing of the human body.…”
Section: Smart Healthcare and Related Methodsmentioning
confidence: 99%
“…Considering that coronary sickness is very fragile to protect time, the time delay between information grouping, far-off transmission, and data accumulating ought to be seen as in the arrangement of information transmission and data storing limit modules. At the same time, to simplify it for the diagnosing expert to make heads or tails of the continuous situation of the patient more, the indispensably visual video transmission work is turned on when basic, and the truly visual video is shipped off the terminal of the astute clinical end system through the distant transmission module [ 15 ]. This module sends the data gathered by the versatile terminal to the data stockpiling and brilliant clinical handling terminal as quickly as time permits, which is more helpful for the acknowledgment of the well-being observing of the human body.…”
Section: Smart Healthcare and Related Methodsmentioning
confidence: 99%
“…Various noninvasive techniques, including valgus braces, canes or shoe soles, and gait modifications, have been employed to mitigate medial contact force (MCF) [4,5]. The role of the lower limb is crucial in delaying the progression of knee osteoarthritis (KOA) [6,7]. Mechanical factors such as contact point, range of motion, and contact force represent key parameters that require evaluation [8].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%